HUBUNGAN LINGKUNGAN KERJA DAN MOTIVASI KERJA DENGAN KINERJA PAMONG BELAJAR DI BP-PAUD DAN DIKMAS JAWA TIMUR - IPUNG RIYAWAN; I KETUT ATMAJA; Suhanadji Suhanadji (JPUS: Jurnal Pendidikan Untuk Semua, 2018)
The need for quality human resources is increasing a demand that can not be postponed again. Improving the quality of human resources (PNS) are a priority. The Government has taken various improvement programs, improving the competence of educators PNF (tutors) had not been optimal, especially in efforts to improve the quality or productivity of its work. The problems that exist are declining performance pegawi (pamog study) annually, based on the results of data obtained ang observation researchers are currently conducting a study. This study aims to describe and analyze (1) how much the relationship between the environment and the performance of Civil Learning (2) how much work motivation and performance of tutors (3) contribute simultaneously between the work environment and work motivation and performance of officials at the BP-ECD and Dikmas Surabaya, east Java.This study uses a quantitative approach to research the type of correlational and multiple regression / double, with a significance level of 5% to know there is a relationship between variables. Because in this research has more than two variables. The process of data collection was done by questionnaire, observation, and documentation. Further data are grouped, analyzed, tested the validity of the data using validity and reliability.The results of data analysis in this experiment showed that (1) there is a relationship between the work environment with the performance of officials learned in early childhood and the BP-East Jwa Dikmas correlation value 0.995 with significance 0.000 <0.05, (2) There is a relationship between work motivation and performance tutors in BP-ECD and Dikmas East Java significance correlation value 0.950 0.000 <0.05 (3) there is a relationship between the working environment and working moivasi with the performance of tutors in BP-ECD and Dikmas East Java with multiple regression constant value amounted to 29.769 value is 0,000. Values closer to 0,000 regression models are getting better at predicting. Then the significance of the F count> F table (16.186 > 3.09). From the analysis of these data we can conclude that there is a relationship apes environment and work motivation and performance of tutors in BP-ECD and Dikmas East Java. Bena so totally relate significantly.